Being in the moment later? Testing the inverse relation between mindfulness and procrastination. (15th April 2019) - Cheung, Rebecca Y.M.; Ng, Melody C.Y.
Abstract: This study examined the longitudinal association between mindfulness and procrastination. A total of 339 Chinese college students participated for four time points, with each time point spanning six months apart. Initial findings based on a cross-lagged panel model suggested an inverse relation between mindfulness and procrastination over time. These findings inform practitioners the importance of cultivating mindfulness as a means to reduce procrastination. Likewise, reducing individuals' tendency to procrastinate can also promote mindful behaviors.